Electrical properties of photosensitive heterostructures n-FeS₂/p-InSe - Tkachuk, I.G.; Orletsky, I.G.; Kovalyuk, Z.D.; Marianchuk, P.D. (Functional Materials, 2018)
Conditions for production of photosensitive anisotypic n-FeS₂/p-InSe heterojunctions by the method of low-temperature spray-pyrolysis of thin films of pyrite on crystalline p-InSe substrates are studied. On the basis of analysis of temperature dependences of direct and reverse VACs (Volt-Ampere Characteristics), the dynamics of the change in energy parameters is established and the role of the energy states at the heterojunction boundary in formation of the contact potential difference is determined. A model of the energy diagram of the heterojunction is proposed, which describes well the electrophysical phenomena observed during the experiment. The mechanisms of formation of direct and return currents through the energy barrier of n-FeS₂/p-InSe are determined.